2021
DOI: 10.1002/pld3.359
|View full text |Cite
|
Sign up to set email alerts
|

Tomato and cotton G protein beta subunit mutants display constitutive autoimmune responses

Abstract: Heterotrimeric G protein Gβ‐deficient mutants in rice and maize display constitutive immune responses, whereas Arabidopsis Gβ mutants show impaired defense, suggesting the existence of functional differences between monocots and dicots. Using CRISPR/Cas9, we produced one hemizygous tomato line with a mutated SlGB1 Gβ gene. Homozygous slgb1 knockout mutants exhibit all the hallmarks of autoimmune mutants, including development of necrotic lesions, constitutive expression of defense‐related genes, and high endog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 88 publications
(127 reference statements)
0
3
0
Order By: Relevance
“…However, the slgb1‐2 and slgb1‐3 mutations were lethal at an early seedling stage (Fig. S9b), similar to previous observations in rice, maize, and tomato (Gao et al ., 2019; Wu et al ., 2020; Ninh et al ., 2021). We therefore generated homozygous slgb1‐1 mutant lines, which carry a 6 bp deletion in the fourth exon of SlGB1 for use in further experiments (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the slgb1‐2 and slgb1‐3 mutations were lethal at an early seedling stage (Fig. S9b), similar to previous observations in rice, maize, and tomato (Gao et al ., 2019; Wu et al ., 2020; Ninh et al ., 2021). We therefore generated homozygous slgb1‐1 mutant lines, which carry a 6 bp deletion in the fourth exon of SlGB1 for use in further experiments (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, other studies have reported that AtGPA1 is not involved in defense against P. syringae or the flg22‐induced ROS burst (Liu et al ., 2013; Torres et al ., 2013), the Arabidopsis Gβ subunit (AtAGB1) plays a positive role in plant defense (Torres et al ., 2013; Liang et al ., 2016; Wang et al ., 2018). In tomato ( Solanum lycopersicum L.), the Gβ subunit (SlGB1) positively regulates the flg22‐induced ROS burst (Ninh et al ., 2021). It is not known, however, whether RGS1 binds to Glc and/or other sugars, or how Glc signaling mechanisms are associated with the regulation of defense, particularly in response to low light intensities.…”
Section: Introductionmentioning
confidence: 99%
“…The susceptibility genes were used to improve pathogen resistance via knocking out the target gene by CRISPR/Cas9 tool in previous studies 24,25 . To create the frameshift mutationinduced CRISPR/Cas9 system for knocking-out genes, the coding regions of the target gene were sequenced to design specific sgRNAs 26,27 . Researchers utilized DNA fragments that could contain a complete or partial open reading frame of the target gene 26 .…”
Section: Design Of Sgrnasmentioning
confidence: 99%
“…Plant G proteins are involved in a wide range of cellular processes, including innate immunity and multiple defense-related responses [18][19][20][21][22][23][24][25][26]. Plants have a limited repertoire of G proteins compared to animals.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the findings from Arabidopsis, studies involving Gβ knockouts in rice, maize, tomato, and cotton, along with the triple XLG knockout in maize, reveal severe autoimmune symptoms. These symptoms comprise heightened PR gene expression, elevated ROS production, and increased seedling lethality [19,[42][43][44]. Such observations suggest that, in these contexts, G proteins might exert a negative influence on PCD processes; however, the underlying mechanism is not established.…”
Section: Introductionmentioning
confidence: 99%